EXPERIMENTAL STUDIES OF OPERATION OF A PNEUMATIC SPRING PRESSURE COMPENSATOR WITH QUASI-ZERO STIFFNESS - Аlеxеy N. Zоtоv (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the research is caused by vibration negative effect on the elements in the installation of the electric centrifugal pump. The presence of vibration increases the number of premature failures. One of the reasons for the vibrational effects on the electric centrifugal pump unit is the pressure drop at the pump discharge, and the frequencies of such fluctuations are small. The main aim of the research is to develop a laboratory installation simulating oscillatory processes occurring on the discharge line of an electric centrifugal submersible pump in a well. Objects: a model of a pneumatic spring pressure compensator with quasi-zero stiffness, structurally representing a pneumatic spring, inside of which there is a package of five sequentially installed disc springs. Methods: numerical solutions of differential equations; theory of oscillations, mathematical analysis, mathematical statistics, methods of mathematical modeling. Results. To confirm the theoretical results obtained by calculation the authors have developed the laboratory facility, which allows studying the system with quasi-zero stiffness. This is is a set of pneumatic spring having a force characteristic with a working area of positive stiffness and a package of sequentially connected disc springs having a force characteristic with a working area of negative stiffness. The parameters of the disk springs were experimentally selected in such a way as to obtain a power characteristic with a region of quasi-zero stiffness at a given pressure in the cylinder sub-piston cavity. To ensure the necessary stability of the system to small changes with the help of the analysis of power characteristics, an optimum number of disk springs is obtained. The authors investigated the power characteristic of a pneumatic compensator with quasi-zero stiffness on the discharge line of an electric centrifugal submersible pump. The result of the research on the laboratory installation was the coincidence with the given error of the oscillation amplitude measurements and theoretically predicted results, which allowed proving the correctness of theoretical conclusions.